Aplikasi Mindfulness untuk mengatasi Stres Akademik dan tinjauan literatur dalam konteks pembelajaran - Marselina, Suci; Murnaka, Nerru P; Maq, Mumu Muzayyin; Amahoru, Archristhea; Fitriana, Septi (Borobudur Educational Review, 2025)
This study aims to review the use of mindfulness applications as a strategy to manage academic stress among students. Academic stress is a common issue faced by students, which can affect their mental health and academic performance. Mindfulness applications have emerged as a practical alternative to help students manage stress more effectively. Through a review of recent literature, this research evaluates various studies that examine the effectiveness of mindfulness in reducing academic stress and supporting psychological well-being. The findings suggest that mindfulness, whether in the form of direct training or digital applications, can significantly reduce academic stress and improve students' mental well-being. Mobile-based mindfulness applications have proven to be effective in providing flexible access for students to practice mindfulness, thereby encouraging consistency and engagement in the practice. However, further research is needed regarding the long-term effectiveness and adaptation of mindfulness applications within the educational context in Indonesia. This study suggests the integration of mindfulness into higher education systems to create a healthier learning environment and support the overall development of students.